2020
DOI: 10.1186/s40792-020-01076-5
|View full text |Cite
|
Sign up to set email alerts
|

A giant pelvic solitary fibrous tumor with Doege–Potter syndrome successfully treated with transcatheter arterial embolization followed by surgical resection: a case report

Abstract: Background Solitary fibrous tumor (SFT), a mesenchymal fibroblastic tumor with a hypervascular nature, rarely develops in the pelvis. Resection of a giant SFT occupying the pelvic cavity poses an increased risk of developing massive hemorrhage during resection, although surgical resection is the most effective treatment method for this tumor to achieve a potential cure. SFT rarely develops with Doege–Potter syndrome, which is known as a paraneoplastic syndrome characterized by non-islet cell tumor hypoglycemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…The promising results obtained so far warrant additional investigations. 37 , 38 Notably, the treatment of vulvar SFT still carries a risk of intraoperative blood loss and postoperative complications including surgical site infection and anal dysfunction 39 ; however, our patient did not develop these complications.…”
Section: Discussionmentioning
confidence: 59%
“…The promising results obtained so far warrant additional investigations. 37 , 38 Notably, the treatment of vulvar SFT still carries a risk of intraoperative blood loss and postoperative complications including surgical site infection and anal dysfunction 39 ; however, our patient did not develop these complications.…”
Section: Discussionmentioning
confidence: 59%
“…Preoperative TAE proved to be of paramount importance to prevent intraoperative bleeding. According to the literature, TAE can be considered a successful and effective technique in preventing intra- and postoperative blood loss, as demonstrated by Yuza and colleagues in surgical excision of giant pelvic solitary fibrous tumors ( 11 ). TAE has proved to be a powerful weapon for avoiding massive bleeding also in oncological orthopedic surgery, such as in resection and reconstruction of long bone hypervascular tumors ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, repeated surgeries for recurrent SFTs or too-large tumors can cause distressful adhesion, and complete surgical resection is considerably challenging [ 15 ]. To avoid a positive surgical margin and reduce operative blood loss, several studies have reported the utility of preoperative transcatheter arterial embolization, as SFTs are usually hypervascular tumors [ 5 , 25 ]. In our case, the main pelvic tumor had grown so large that the tumor had severe adhesion to the rectum and the left ureter, so it might have been wise to consider preoperative transcatheter arterial embolization followed by surgery.…”
Section: Discussionmentioning
confidence: 99%